Novel biomarkers: the RUNX family as prognostic predictors in colorectal cancer - Liu, Yingting; Chen, Junjun; Li, An; Wu, Yue; Ge, Junwei; Yuan, Maoling; Xu, Bin; Zheng, Xiao; Chen, Lujun; Jiang, Jingting (Frontiers in Immunology, 2024)
While biomarkers have been shown to enhance the prognosis of patients with colorectal cancer (CRC) compared to conventional treatments, there is a pressing need to discover novel biomarkers that can assist in assessing the prognostic impact of immunotherapy and in formulating individualized treatment plans. The RUNX family, consisting of RUNX1, RUNX2, and RUNX3, has been recognized as crucial regulators in developmental processes, with dysregulation of these genes also being implicated in tumorigenesis and cancer progression. In our present study, we demonstrated a crucial regulatory role of RUNX in CD8+T and CD103+CD8+T cell-mediated anti-tumor response within the tumor microenvironment (TME) of human CRC. Specifically, RUNXs were significantly differentially expressed between tumor and normal tissues in CRC. Patients with a greater proportion of infiltrating CD8+RUNX1+, CD103+CD8+RUNX1+, CD8+RUNX2+, CD103+CD8+RUNX2+, CD8+RUNX3+, or CD103+CD8+RUNX3+ T cells demonstrated improved outcomes compared to those with lower proportions. Additionally, the proportions of infiltrating CD8+RUNX1+T and CD8+RUNX3+T cells may serve as valuable prognostic predictors for CRC patients, independent of other clinicopathological factors. Moreover, further bioinformatic analysis conducted utilizing the TISIDB and TIMER platforms demonstrated significant associations between the members of the RUNX family and immune-infiltrating cells, specifically diverse subpopulations of CD8+TILs. Our study of human colorectal cancer tissue microarray (TMA) also revealed positive and statistically significant correlations between the expressions of RUNX1, RUNX2, and RUNX3 in both CD8+T cells and CD103+CD8+T cells. Our study comprehensively revealed the varied expressions and prognostic importance of the RUNX family in human colorectal cancer tissues. It underscored their potential as vital biomarkers for prognostic evaluation in colorectal cancer patients and as promising targets for immunotherapy in treating this disease.